Risk factors in addition to short and long-term outcomes with thin catheter surfactant administration failure in preterm infants: a retrospective analysis - Kanmaz Kutman, Hayriye Gözde; Siyah Bilgin, Betül; Büyüktiryaki, Mehmet; Kadıoğlu Şimşek, Gülsüm; Üstünyurt, Zeynep; Canpolat, Fuat Emre (My University, 2025)
Objective: To evaluate the incidence of thin catheter surfactant administration (TCA) failure and compare short and long-term neonatal outcomes who failed TCA or did not. Design: Single-center retrospective cohort study. Infants between 25 and 30 weeks of gestational age with respiratory distress syndrome and receiving 200 mg/kg poractant alfa via thin catheter administration were included. TCA failure was defined as the need for early mechanical ventilation (< 72 h). Infants were divided into two groups those who failed TCA or those who did not. Results: The TCA failure rate was 24.6%. Initial oxygen requirement (0.39% vs. 0.36%) and the number of small for gestational age infants were significantly higher in the TCA failure group (15% vs. 7.9%). Infants who failed TCA had a higher pneumothorax (6.7% vs. 1.1%, p = 0.03), BPD (15% vs.5.5%, p = 0.02), late-onset sepsis (36.7% vs. 18%, p = 0.04), retinopathy of prematurity rates (11.7% vs. 3.3%, p = 0.02) and an increased duration of respiratory support. However, Bayley Scales of Infant Development II scores were comparable between groups at 18 and 26 months of corrected age. Conclusion: Infants who fail TCA are at increased risk for short-term complications despite favourable long-term neurodevelopmental outcomes. Identifying infants at risk of TCA failure may help early prevention of morbidities and individualise their management.
Keywords: Biological Products; Infant; Newborn; Premature; Respiratory Distress Syndrome; Risk Factor; Treatment Failure